Coastal resources economics and ecosystem valuation - J. Walter Milon; Sergio Alvarez (MDPI, 2019)
The practical importance of economic valuation information can hardly be overstated. Coastal and marine resource policy planning and management benefit from complete information on the impact of policy decisions. In addition, proper accounting of the impacts of these policy decisions is necessary for benefit-cost analyses and measurements of economic growth over time. This special issue focuses on economic valuation of coastal and marine ecosystem services. Economic valuation provides methods and techniques to determine how changes in coastal and marine ecosystem services can be translated into benefits and costs to society. Economic values play an important role in everyday life and provide useful information about human welfare and happiness. Valuation provides a consistent framework to understand human-nature interactions across a broad range of coastal and marine resources, and to evaluate the costs and benefits of these interactions. The focus on ecosystem services provides new research on this perspective of human-nature interactions that has profoundly changed the academic dialogue on natural systems, but has had limited impact on public dialogue and the policy process.
Keywords: 330